Compositional changes in cell wall polysaccharides from apple fruit callus cultures modulated by different plant growth regulators - Alayón-Luaces, Paula (Plant science : an international journal of experimental plant biology, 2012)
Copyright © 2011 Elsevier Ireland Ltd. All rights reserved.